PENGARUH GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN MELALUI STRUKTUR MODAL (pada Perusahaan Sektor Property, Real Estate & Building Construction yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2014) - Nova Adhitya Ananda; I Nyoman Nugraha Ardana P (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2016)
ABSTRACT The purpose of this research is to find the influence of growth opportunity and capital structure on firm value. The research objects used is property, real estate and building construction company which listed in Indonesian Stock Exchange in 2011-2014. This research used a purposive sampling technique in determining the research sample. The number of companies chosen as the sample in 37 company of 54 companies registered in property, real estate and building construction sector. This research was included in the explanatory research using quantitative approach. Data analysis method used in this research is partial least square (PLS) analysis. The result showed that in directly growth opportunity and capital structure has a significant effect on firm value. Growth opportunity undirectly has significant effect on the firm value by means of capital structure. Growth opportunity has a positive and significant effect on capital structure and capital structure has a negative and significant effect on firm value.Keywords : Growth Opportunity, Capital Structure and Firm Value